1994
DOI: 10.1007/bf03222640
|View full text |Cite
|
Sign up to set email alerts
|

The combustion synthesis of advanced materials

Abstract: This article discusses the versatility of utilizing exothermic combustion synthesis reactions to produce ceramic, intermetallic, and composite materials in a one-step process. The emphasis is placed on controlling the reaction parameters of these exothermic synthesis reactions as a means of control/ing the microstructure and properties of the sYI1-thesized materials and composites. The applicatiol1 of this technology to the synthesis and control of a selection of advanced materials is demonstrated (i.e. , dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…In fact, foamed TiC materials with as high as 97 pct porosity were obtained under low gravity when a volatile component was added to the Ti ϩ C reactant mix. [6] In the SHS of metal-ceramic composites, Moore et al observed similar results, [7] while density-driven sedimentation was observed in the SHS of Ni 3 Al-TiB 2 composites. [8] This article presents the effect of gravity on the SHS of Ni 3 Ti-TiB 2 and Al-HfB 2 composites.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…In fact, foamed TiC materials with as high as 97 pct porosity were obtained under low gravity when a volatile component was added to the Ti ϩ C reactant mix. [6] In the SHS of metal-ceramic composites, Moore et al observed similar results, [7] while density-driven sedimentation was observed in the SHS of Ni 3 Al-TiB 2 composites. [8] This article presents the effect of gravity on the SHS of Ni 3 Ti-TiB 2 and Al-HfB 2 composites.…”
Section: Introductionsupporting
confidence: 64%
“…Under ideal conditions, the average settling rate of the HfB 2 partcles in the aluminum matrix as calculated from Equation [7] was about 6.2 m/s. From the temperature profiles, the samples remained in the liquid state for 20 to 30 seconds, the total settling distance thus should be in the 120-to 180-m range.…”
Section: B Sedimentation Of the Ceramic Phasesmentioning
confidence: 99%
“…When a composite consisting of two or more phases is synthesized by SHS, settling of the higher density phase will occur resulting in a nonuniform microstructure. [9,10] Processing of composite materials, either MMCs, intermetallic matrix composites (IMCs), or ceramic matrix composites (CMCs), by means of SHS has gained wide interest. While there is relatively little difficulty in producing CMCs and IMCs using SHS, synthesizing MMCs using SHS has proved to be difficult since such reactions are weakly exothermic, especially when a large amount of metal phase is present in the composite.…”
Section: Introductionmentioning
confidence: 99%
“…A great advantage for the MMCs produced by SHS over the traditional melting-casting route is that the ceramic particles formed in situ during the SHS process are extremely fine, hence offering potential for superior mechanical properties. [2][3][4][5][6][7][8][9][10][11][12][13][14] The work reported in this article is concerned with the synthesis of the Ni 3 Ti-TiB 2 IMCs by means of SHS. This system was selected since the specific gravity of TiB 2 is approximately half that of Ni 3 Ti and, therefore, can be subsequently used to evaluate the role of gravity in the distribution of this lighter, solid ceramic reinforcing phase within the heavier Ni 3 Ti liquid matrix phase.…”
Section: Introductionmentioning
confidence: 99%
“…Professor Moore's research interest has been on the formation of composite materials at normal or reduced gravity environments. The recent research interest of Professor Moore is focused on the formation of biomaterials [189][190][191][192]. Professor Moore is very actively involved in numerous professional societies and his published contributions into the field of SHS are highly regarded by the international SHS community.…”
Section: Combustion Synthesis Research In Usa After 1980mentioning
confidence: 99%